EFFECT OF RETURN ON INVESTMENT, FINANCIAL LEVERAGE, BOOK VALUE PER SHARE, DIVIDENDS ON THE STOCK PRICE SECTOR MANUFACTURING COMPANY IN INDONESIA STOCK EXCHANGE - Dody Kurniawan, 0835030729; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2013)
This study aims to analyze the influence of Return On Investment, Financial Leverange, PerShare Book Value, and Dividends on stock prices at the companys manufacturing sector in Indonesia Stock Exchange.This population is a manufacturing company located in the BEI, the sample selection criteria specified in the acquired 12 companies, the method used multiple linear regression analysis.The test results obtained that there is a significant and positive between Return On Investment, Leverange, Book Value Per Share of Stock prices partially, and other results obtained no significant effects between the dividend to the stock price partially. And simultaneously Return On Investment, Leverage, Book Ratio Per Share and Stock Dividend influence.Keywords: Return On Investment, Dept to Equity Ratio, Book Ratio Per Share, Dividend and Stock Price.